REDES SOCIAIS DE UM E DOIS MODOS: TRAJETÓRIA DA PRODUÇÃO CIENTÍFICA DO ENCONTRO DE ENSINO E PESQUISA EM ADMINISTRAÇÃO E CONTABILIDADE - Henrique César Melo Ribeiro (Universidade Federal de Santa Catarina, 2019)
The objective of this study was to analyze the trajectory of the scientific production of articles published in the Meeting of Teaching and Research in Administration and Accounting during the years of 2007, 2009, 2011, 2013 and 2015. Methodologically, of social networks in one and two modes in 520 identified articles. In the one-mode social network of the HEIs, focusing on the degree, the USP and UFRGS stood out. Regarding the two-mode social network (authors and IES), USP was again highlighted, followed by institutions: UFU, UFSC, UFPE, UFMG, UFLA and UFBA. Still, with regard to social networking in two ways, now, highlighting the authors and themes, the following themes emerge: teaching cases, student training, teaching in administration, learning strategies, distance education, teaching-learning, research scientific management, business strategy, stricto sensu postgraduate in management and academic skills. It is generally concluded that the present study evidenced, from a different perspective, the scientific production of the articles evidenced in the EnEPQ, thus manifesting data, information, knowledge and contemporary knowledge about said congress and, consequently, on the said area of the knowledge, contributing to their better understanding and understanding in the national scientific literature.